(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To compare the efficacy of Diclofenac sodium and Pregablin in reducing post operative pain in patients with surgeries around the knee. Methods: This randomized controlled trial was conducted in Department of Orthopedics Surgery and Traumatology Mayo Hospital Lahore from 23rd December 2017 to 23rd December 2020. All adults patients of either gender and age with surgeries around the knee fulfilling the inclusion criteria were randomly divided into two equal groups as group A (Diclofenac sodium 50 mg BD) and group B (Pregablin 75 mg BD). The drugs were administered orally for two days after surgery. Post operative pain intensity was determined with visual analogue score (VAS). Comparison of VAS in both group was done and P value calculated with paired-t test. P value < 0.05 was considered significant. Results: The total number of patients were 80 and equally divided into group A and group B. In group A 26 (65%) were male and 14 (35%) were females. In group B 25 (62.5%) were male and 15 (37.5%) females. The mean age of group A patients was 30.5±7.33 and group B 31.15±9.97 years. The mean VAS in group A was 4.08±0.95 and in group B was 4.012±0.96 (P value 0.5) on first post-operative day. On second post-operative day group A had mean VAS 4.012±0.96 and group B 1.55±0.59.(P value 0.001) Conclusion: Post-operative oral Pregablin is more effective than Diclofenac sodium in reducing postoperative pain in patients with surgeries around the knee.